Direct determination of selenium(IV) in biological samples by cathodic-stripping voltammetry - Ahmad, Rahmalan; Hill, John O.; Magee, Robert J. (Royal Society of Chemistry, 1983)
The use of a commercially available digesting solvent, Lumatom, for the determination of selenium(IV) in biological samples using cathodic-stripping voltammetry is reported. It was found possible to determine selenium directly in biological samples containing metals such as arsenic(III), copper(II), lead(II), iron(III) and zinc(II). The results for selenium in bovine liver and oyster tissue are reported.